Perceived teacher support, self-concept, enjoyment and achievement in reading: A multilevel mediation model based on PISA 2018 - Ma, Lihong; Luo, Haifeng; Xiao, Leifeng (Learning and individual differences, 2021)
Based on expectancy-value theory, this research examined the link between student-perceived teacher-support and reading literacy via multiple mediation effect of reading self-concept and reading enjoyment with a Chinese sample of PISA 2018. Student-reported measures of teacher support, reading enjoyment and reading self-concept, and standardized tests of reading literacy were adopted. Multilevel mediation analysis showed that the direct effect of student-perceived teacher support on reading literacy is not significant at the school level, but significant at the student level, and the indirect effect of student-perceived teacher support on reading literacy through reading enjoyment, reading self-concept, first reading self-concept and then reading enjoyment is significant both at the student level and at the school level with SES and gender controlled. The present results indicate that perceived teacher support is beneficial to student learning by fostering academic self-concept and academic enjoyment. The current results have significant practical implications for teaching practices. •The link between perceived teacher support and reading literacy is mediated by reading enjoyment.•The link between perceived teacher support and reading literacy is mediated by reading self-concept.•The link between perceived teacher support and reading literacy is serially mediated by self-concept and then enjoyment.